The Relationship Between Meteorological and Dengue Fever Prevalence at Tanjung Priok Health Center, North Jakarta (2018-1014): An Islamic Perspective - Zahwa Aisya Nabila Ajedo; Ambar Hardjanti; Afrizal Tw (Eduvest - Journal of Universal Studies, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a major public health problem in Indonesia, particularly in tropical regions such as North Jakarta. Meteorological factors, including air temperature, humidity, rainfall, and wind speed, play an important role in the spread of this disease because they affect the life cycle and activity of the Aedes aegypti mosquito vector. The high number of DHF cases in the Tanjung Priok area over the years is thought to be influenced by variations in these dynamic climatic factors. This study was an analytical observational study with a cross-sectional design using secondary data. Data on DHF cases were obtained from the annual reports of the Tanjung Priok Health Center, while meteorological data (air temperature, humidity, rainfall, and wind speed) were collected from NASA. Data analysis was performed using multiple linear regression tests to determine the relationship between meteorological factors and DHF prevalence. The results showed that the meteorological factor that had a significant effect on the prevalence of DHF was wind speed (p = 0.046). Meanwhile, air temperature (p = 0.902), humidity (p = 0.562), and rainfall (p = 0.528) did not show significant relationships. The increase in wind speed can extend the flying range of Aedes aegypti mosquitoes, thereby increasing the potential for DHF transmission in densely populated areas. This study concludes that there is a significant relationship between wind speed and the prevalence of DHF in the Tanjung Priok Health Center area, North Jakarta.